Skin Color and Maternal Near Miss: Exploring a Demographic and Health Survey in Brazil - Karayna Gil Fernandes; Maria Helena Sousa; José Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose In 2013, it was estimated that 289,000 maternal deaths occurred worldwide. The maternal mortality ratio has decreased in many countries in the past decades, due to early identification and treatment of obstetric complications, despite the dissimilarities observed in diverse locations and populations. Black women, for instance, have always been more susceptible to the occurrence of maternal mortality and severe morbidity. Therefore, the objective of this study is to assess skin color as a predictive factor for maternal near miss (MNM) in a sample of Brazilian women interviewed in the Brazilian National Demographic and Health Survey (DHS) of 2006. Method A secondary analysis of the DHS database, a population-based crosssectional nationally representative study was conducted. This database is of public domain. The risk of maternal complications according to ethnic group and the associated sociodemographic characteristics were evaluated. For the data analysis, the odds ratios and respective 95% confidence intervals were calculated. Results In the sample interviewed, 59% of women were black or brown (mixed-race). Approximately 23% of women had some complication, and 2% of these women had at least one MNM pragmatic criterion. The MNM rate was 31 per 1,000 live births, and its occurrence was not statistically different among the ethnic groups. The only factors identified that were considered to be associated with the occurrence of MNM were maternal age above 40 and women not currently attending school, but only among white women. Conclusion The 2006 DHS results did not show a higher occurrence of maternal complications, and specifically of MNM associated with black/brown skin color.